2019
DOI: 10.1021/acs.jchemed.9b00752
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Wavelength Dependence of Photochemical Reactions: Cutting-Edge Research in the Teaching Lab

Abstract: The prompt transfer of cutting-edge science into students’ curricula is a challenging task. Often research experiments are too complex or expensive to be translated into a secondary or tertiary education setting. Herein, we introduce a laboratory experiment that translates the recently developed research technique of a wavelength dependent, photochemical action plot into a student accessible format. The practical incorporates aspects of photophysics, required to calculate a constant photon emission from each d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In order to gain insight into the light-harvesting properties of dyes, students collect the UV–vis and emission spectra of 4 in CH 2 CI 2 as shown in Figures and . The absorption spectrum of the dye molecule is red-shifted and extends in the visible region showing that it is able to absorb solar energy (Figure ). The red-shifting of the spectrum for 4 is attributed to the narrowing of the HOMO–LUMO band gap due to the attachment of the pyrene molecules to the triphenylamine donor moiety which increases its conjugation and enhances its electron-donating properties. The concept of narrowing the HOMO–LUMO gap to lengthen the absorption wavelength is normally taught in the second year of organic chemistry on the topic “Conjugated Dienes and Ultraviolet Spectroscopy”. Therefore, this principle is reinforced during this part of the project.…”
Section: Resultsmentioning
confidence: 99%
“…In order to gain insight into the light-harvesting properties of dyes, students collect the UV–vis and emission spectra of 4 in CH 2 CI 2 as shown in Figures and . The absorption spectrum of the dye molecule is red-shifted and extends in the visible region showing that it is able to absorb solar energy (Figure ). The red-shifting of the spectrum for 4 is attributed to the narrowing of the HOMO–LUMO band gap due to the attachment of the pyrene molecules to the triphenylamine donor moiety which increases its conjugation and enhances its electron-donating properties. The concept of narrowing the HOMO–LUMO gap to lengthen the absorption wavelength is normally taught in the second year of organic chemistry on the topic “Conjugated Dienes and Ultraviolet Spectroscopy”. Therefore, this principle is reinforced during this part of the project.…”
Section: Resultsmentioning
confidence: 99%
“…To further reduce the error, we also replaced the computer screen with a commercial white LED flat light source with higher brightness and remeasured the H value of copper nitrate solutions with different concentrations. It was found that the H value still did not change with the concentration.…”
Section: Experimental Verificationmentioning
confidence: 99%
“…For comparison, the results of ref 1 are also shown in the figure (denoted by "○"), which demonstrates that its H value increased significantly with the increase of concentration. To further reduce the error, we also replaced the computer screen with a commercial white LED flat light source with higher brightness 5 and remeasured the H value of copper nitrate solutions with different concentrations. It was found that the H value still did not change with the concentration.…”
Section: ■ Experimental Verificationmentioning
confidence: 99%
“…To date, the majority of the setups which have been implemented in teaching laboratories require a photochemical chamber for irradiation of the sample ex situ. In addition, such setups are predominantly based on the use of visible light which limits their application to the photochemistry of rather large polyaromatic compounds and does not probe the reaction progression as a function of time delay. …”
Section: Introductionmentioning
confidence: 99%